The effects of Chinese Yam-Epimedium mixture on respiratory function and quality of life in patients with chronic obstructive pulmonary disease - 赵亚玲 宋鸿儒 费晋秀 梁英 张兵华 刘秋平 王娟 胡平 (Journal of traditional Chinese medicine, 2012)
OBJECTIVE：To examine the clinical effects of a mixture of Chinese Yam and Epimedium in patients with stable moderate or severe chronic obstructive pulmonary disease（COPD）.METHODS：Forty-nine patients with COPD were randomly allocated to a group whose usual treatment was supplemented with oral Chinese Yam-Epimedium mixture,or a control group given placebo.For each patient,body mass index,airflow obstruction,dyspnea,and exercise capacity were measured and converted into the BODE index before treatment and at one and three months after initiation of treatment.Participants also completed the St George＇s Respiratory Questionnaire（SGRQ） at the same intervals.RESULTS：After one month,improvements were seen in the BODE index and SGRQ of participants taking Chinese Yam-Epimedium mixture compared to controls.There were statistically significant differences in the SGRQ：three of its components and the total SGRQ scores were significantly decreased（P〈0.05）,respiratory symptom scores had improved（P〈0.01）,and the dyspnea component of the BODE index had significantly decreased（P〈0.05）.Similar improvements were observed after three months of treatment,but exercise tolerance had also improved：the six-minute walking distance had significantly increased（P〈0.05） in the treatment group when compared with controls.CONCLUSION：Chinese Yam-Epimedium mixture can significantly improve dyspnea,exercise capacity,and the quality of life of patients with stable moderate or severe COPD.